The Role of Managerial Ownership as Moderating the Effect of Profitability, Accounting Prudence, and Tax Planning on Firm Value - Safna Rahmah Indrayni; Alfiati Silfi; Mudrika Alamsyah Hasan (Jurnal Akuntansi dan Perpajakan, 2025)
Investors' views on the successful performance of a company are reflected in the company's value, which is generally influenced by fluctuations in the market share price. Throughout the current year, the stock prices of companies engaged in the raw material production sector have decreased consistently. The purpose of this study is to analyze the effect of profitability, accounting prudence, and tax planning on firm value and evaluate the role of managerial ownership as a moderating variable in this relationship in raw material producing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study involved a population of 311 companies, with a sample of 81 companies observed for three years, resulting in a total of 243 observation data. The sample selection in this study was carried out using purposive sampling method, while data analysis was carried out by applying multiple linear regression and moderation regression. The findings in this study indicate that profitability, accounting prudence, and tax planning have an influence on firm value. Managerial ownership is proven to moderate the effect of profitability and accounting prudence, but does not moderate the effect of tax planning on firm value. These results imply that future researchers are advised to explore other moderating variables that are more relevant in moderating the effect of tax planning on firm value, considering that managerial ownership does not show a significant moderating role in this effect.